Evolution Of Multidrug-Resistant Acinetobacter Baumannii Pneumonia In Years In Terms Of Tigecycline Treatment - Merve Mert Vahabi; Deniz Akyol; Deniz Dağ; Şevket Yeniyol; Olcay Buse Kenanoğlu; Oğuzhan Acet; Ayşe Uyan Önal; Uğur Önal; Seichan Ketentzi; Gamze Şanlıdağ; Gunel Quliyeva; Şükrü Dirik; et al. (Journal of Global Antimicrobial Resistance)
BACKGROUND-AIM: Herein, we aimed to evaluate and compare the efficacy and susceptibility patterns of tigecycline in MDR A.baumannii pneumonia (MDRABP) in a recent vs retrospective cohort. METHODS: The outcome of adult (>18 years old) patients who were consulted by Infectious Diseases consultants due to culture proven MDRABP and treated with tigecycline between March 2016 and October 2023(Group B) was compared with a similar previously published retrospective cohort from our center(Group A, Published J Chemother. 2011 dec;23(6):345-9). Statistical analysis was performed via Chi square test and a p value less then 0.05 was considered significant. RESULTS: There were total of 202 cases of MDRABP(72 patients in group a and 130 patients in Group B). Forty-seven and 81 cases were considered as VAP in group A and B, respectively. Tigecycline and netilmicin susceptibility were significantly less in group b(Table). C/S combination and tigecycline monotherapy were significantly more common in group A while any combination therapy, colistin, fosfomycin and polymyxin b combination were more common in group B (p<0.05 table). Group A EOT microbiologic eradication was significantly higher in the overall cohorts as well as HAP and VAP subgroups(Table). In the combined data of group A and B microbiological response was similar in tigecycline sensitive vs. intermediately-sensitive strains (41/94-43.6% vs.22/48-45.8% p:0.801). Not overall clinical success but clinical success in combination therapy subgroup was significantly lower in group B(Table). CONCLUSION: Our findings show that tigecycline resistance rates in MDRABP increased during years. Microbiological eradication rates but not clinical outcomes decreased significantly.